A revised 1000 year atmospheric δ13C-CO2 record from Law Dome and South Pole, Antarctica - Rubino, M; Etheridge, DM; Trudinger, CM; Allison, CE; Battle, MO; Langenfelds, RL; Steele, LP; Mark Curran; Bender, M; White, JWC; Jenk, TM; Blunier, T; et al. (2013)
We present new measurements of δ13C of CO2 extracted from a high-resolution ice core from Law Dome (East Antarctica), together with firn measurements performed at Law Dome and South Pole, covering the last 150 years. Our analysis is motivated by the need to better understand the role and feedback of the carbon (C) cycle in climate change, by advances in measurement methods, and by apparent anomalies when comparing ice core and firn air δ13C records from Law Dome and South Pole. We demonstrate improved consistency between Law Dome ice, South Pole firn, and the Cape Grim (Tasmania) atmospheric δ13C data, providing evidence that our new record reliably extends direct atmospheric measurements back in time. We also show a revised version of early δ13C measurements covering the last 1000 years, with a mean preindustrial level of −6.50‰. Finally, we use a Kalman Filter Double Deconvolution to infer net natural CO2 fluxes between atmosphere, ocean, and land, which cause small δ13C deviations from the predominant anthropogenically induced δ13C decrease. The main features found from the previous δ13C record are confirmed, including the ocean as the dominant cause for the 1940 A.D. CO2 leveling. Our new record provides a solid basis for future investigation of the causes of decadal to centennial variations of the preindustrial atmospheric CO2 concentration. Those causes are of potential significance for predicting future CO2 levels and when attempting atmospheric verification of recent and future global carbon emission mitigation measures through Coupled Climate Carbon Cycle Models.